Peningkatan Kapasitas Kelompok Wanita Tani Dalam Pengembangan Sumber Daya Manusia di Daerah Sudiang Makassar - Andi Arwinda Wildam; Akmal Umar; Nurhaedah Nurhaedah; Syahrir Syahrir; Edi Jusriadi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This Community Service activity aims to increase the capacity of women farmer groups (KWT) in developing human resources (HR) in the agricultural sector. KWT plays a crucial role as agents of change in improving food security and family welfare. However, limited knowledge, managerial skills, and access to technology are often major obstacles. The research method used was a qualitative approach with a case study technique. Data were collected through participant observation, in-depth interviews, and Focus Group Discussions (FGDs) with KWT members. The results showed that capacity building can be achieved through several strategies, including: 1) Continuous training on innovative cultivation techniques, financial management, and agricultural product marketing; 2) Intensive mentoring by agricultural extension workers in implementing new practices; and 3) Facilitating access to resources such as capital, market information, and appropriate technology. This capacity building not only increases agricultural productivity but also strengthens women's economic independence, self-confidence, and strategic roles in decision-making at the community level. Thus, strengthening KWT in human resource development is an important investment to realize a more sustainable and gender-equitable agriculture. Furthermore, this community service activity highlights the importance of community participation in maintaining the program's sustainability. Active participation by KWT members in every stage of the program, from planning to evaluation, is crucial to ensuring that the program is tailored to local needs and conditions. Through collaboration between KWT, agricultural extension workers, and various other stakeholders, such as microfinance institutions and local governments, it is hoped that an ecosystem will be created that supports the growth and development of an inclusive and sustainable agricultural sector. This program is expected to have a long-term impact, not only on the welfare of KWT members but also on improving food security at the community level.